Are patterns of family evening meal practices associated with child and parent diet quality and weight-related outcomes?. (1st April 2022) - Lee, Jiwoo; Friend, Sarah; Horning, Melissa L.; Linde, Jennifer A.; Flattum, Colleen; Lindberg, Rebecca; Fulkerson, Jayne A.
Abstract: Family meal practices such as family member presence, fast food consumption and media usage have been associated with health outcomes. However, little is known about combinations of family meal practices and their effects on diet and health. This secondary data analysis aimed to identify patterns of family evening meal practices and examine their associations with family characteristics (e.g., demographics and chaos) and child and parent diet quality and weight-related outcomes. We used baseline data from a community-based randomized controlled trial with 7- to 10-year-old children and their parents in rural Minnesota (n = 114). Parent-reported structural (e.g. media usage) and interpersonal (e.g. mealtime routines) aspects of family evening meal practices were included in latent profile analyses to identify patterns. Diet quality was assessed by child Healthy Eating Index-2015 and parent fruit and vegetable intake. Weight-related outcomes were determined using measured body mass index (z-scores) and percent body fat. A 3-class model was the model of best-fit. The Unplanned Infrequent Family Evening Meals with Mixed Healthfulness class (C1) featured the least frequent family evening meals and the lowest scores for mealtime routines and planning skills. The Family Evening Meals with Fast Food class (C2) characterized having family evening meals four times a week, but fast food was often served. The Planful, Healthful and Frequent Family Evening Meals class (C3) reported the highest meal routine and planning scores as well as frequent family evening meals. Parents in C3 had higher consumption of fruits and vegetables and children in C3 had lower percent body fat, compared to those in other classes. Distinctly different patterns of family evening meal practices suggest a need for considering heterogeneity of family evening meal practices in developing tailored family-meal interventions.